Investigation and Improvement of Bursting Force Equations in Posttensioned Anchorage Zone - Young Hak Lee; Min Sook Kim (Advances in Materials Science and Engineering)
In posttensioned concrete members, the high local stress under the anchorage causes transverse tensile stress. Therefore, it is very important to predict the bursting force to determine appropriate reinforcement details. In the present work, the existing equations of the bursting force for the anchorage zone were evaluated and an equation for the bursting force based on finite element analysis was proposed to improve the model’s accuracy. Parametric analysis was performed considering the anchorage shape, tendon angle, and eccentric distance. The analytical results indicate that the existing equations underestimate or overestimate the bursting force. The proposed equation is able to predict the bursting force reasonably well for an anchorage zone with rectangular bearing plate, cavity, and eccentric distance.